Early Cambrian Anabarella plana from Three Gorges area, South China - Qiang, Yaqin; Peng, Jiaxin; Song, Zuchen; Sun, Jie; Zhao, Xiaofang; Li, Guoxiang; Han, Jian; Guo, Junfeng (Frontiers in Earth Science, 2023)
Anabarella, one characteristic taxon of early molluscs, widely distributed in the early Cambrian strata and was considered as an important link in the evolutionary lineage reflecting a transitional form from helcionelloids to bivalves. In South China, Anabarella was mainly documented from Yunnan, Shaanxi, Sichuan and Hubei provinces. However, the taxonomy and occurrences of Anabarella are questionable. New and abundant well-preserved helcionelloid mollusc Anabarella were recovered from Member 5 of the Yanjiahe Formation in Three Gorges. Through morphological study, these specimens can be definitely identified as A. plana. On the basis of new material, the species of Anabarella previously reported in the literature from South China were taxonomically revised, and except for A. plana from the Yanjiahe Formation, other species should be assigned to Igorella. Therefore, at present, A. plana is the only valid identification species of the genus Anabarella in South China, which is limited to Cambrian Stage 2. On the specimens of A. plana, three types of microstructures are recognized: convex polygonal impressions, concave polygons, and lamello-fibrillar microstructure. Compared with W. crosbyi, the similarity in morphology and shell microstructures of A. plana indicates the close evolutionary relationship between them. In addition, according to the International Code of Zoological Nomenclature (principle of priority), the latter genus Anabarella, which was established for conifer linear leaves from the Cretaceous, is invalid.